2008
DOI: 10.1007/s00199-008-0344-x
|View full text |Cite
|
Sign up to set email alerts
|

Oligopoly with a large number of competitors: asymmetric limit result

Abstract: Stackelberg game, Cournot game, Limit result, Marginal-cost advantage, Arrow effect, L11, L12, L13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“… P ( X *( X L , n )) uniformly converges to min { C ′(0), P ( X L )} ( P with a price ceiling at C ′(0)) on . The proof is similar to in section 3.2 of Ino and Kawamori (2009). This implies that converges to zero as n →∞ for any sequence { Y ( n )} where .…”
mentioning
confidence: 66%
See 3 more Smart Citations
“… P ( X *( X L , n )) uniformly converges to min { C ′(0), P ( X L )} ( P with a price ceiling at C ′(0)) on . The proof is similar to in section 3.2 of Ino and Kawamori (2009). This implies that converges to zero as n →∞ for any sequence { Y ( n )} where .…”
mentioning
confidence: 66%
“…For an application of the Stackelberg model with free entry of followers to innovation and trade policy, see Etro (2004, 2011). For the limit result when an infinite number of followers enter the market, see Ino and Kawamori (2009). For the implications of public policy in free‐entry markets, see Davidson and Mukherjee (2007), Brandão and Castro (2007), Mukherjee and Mukherjee (2008), and Marjit and Mukherjee (2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Kamien and Tauman (2002) extended his model to a Cournot oligopoly market. With a general demand function and convex cost, Ino and Kawamori (2009) examined whether or not a cost-reducing innovation is profitable for the incumbent patent holder in a large oligopolistic market, and showed that a partial-monopoly market, in which the incumbent patent holder chooses his output as a price maker while the other firms produce as price takers, arise when he does not license his (non-drastic) patented technology. It is left for a future research to study bargaining outcomes in the case of an incumbent patent holder.…”
Section: The Incumbent Patent Holdermentioning
confidence: 99%